Students’ Perceptions toward Project-Based Learning in English Vocabulary Learning at the Eighth Grade of SMP Kristen Bala Keselamatan Palu - Nadrun Nadrun; Budi Budi; Mochtar Marhum (Journal of English Language and Education, 2026)
This study investigates students’ perceptions toward the implementation of Project-Based Learning (PjBL) in English vocabulary learning at the eighth grade of SMP Kristen Bala Keselamatan Palu. This study employed a mixed-methods design. Data were collected through a questionnaire distributed to 28 students and semi-structured interviews with selected students to obtain deeper insights into their learning experiences. The findings reveal that students generally have positive perceptions of Project-Based Learning. Project activities help students understand and remember vocabulary more easily, increase their motivation to learn English, encourage collaboration during group work, and enhance their confidence in using English. However, several challenges were identified, including unclear instructions, unequal participation among group members, and the longer time required to complete project tasks. Overall, the study concludes that Project-Based Learning provides meaningful learning experiences and effectively supports English vocabulary learning in EFL classrooms.